Search for pair production of second generation scalar leptoquarks in p(p)over-bar collisions at root s-=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (Elsevier B.V., 2006)
We report on a search for the pair production of second generation scalar leptoquarks (LQ(2)) in p (p) over bar collisions at the center-of-mass energy, root s = 1.96 TeV, using data corresponding to an integrated luminosity of 294 19 pb(-1) recorded with the DO detector. No evidence for a leptoquark signal in the LQ(2)LQ(2) -> mu q mu q channel has been observed, and upper bounds on the product of cross section times branching fraction were set. This yields lower mass limits of m(LQ2) > 247 GeV/c(2) for beta = B(LQ(2) -> mu q) = 1 and m(LQ2) > 182 GeV/c(2) for beta = 1/2. Combining these limits with previous DO results, the lower limits on the mass of a second generation scalar leptoquark are m(LQ2) > 251 GeV/c(2) and m(LQ2) > 204 GeV/c(2) for beta = I and beta = 1/2, respectively. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: second generation leptoquarks